An interactional analysis of one-to-one pastoral care delivery within a primary school. (2nd January 2017) - Bradley, Louise; Butler, Carly W.
Abstract: Despite an interactional analysis being able to offer valuable insight into the institutional workings of pastoral care practice, pastoral care delivery remains largely unstudied. This paper will contribute new knowledge to the field of counselling and education by offering an interactional analysis of one-to-one pastoral care provision within a primary school. Much pastoral care practice is informed by theory, often accompanied by guidelines about how to deliver pastoral care activities effectively. The pastoral carer needs to convert these guidelines into talk in order to deliver the intervention as an interactional encounter. However useful these guidelines are, they cannot show what the actual delivery of those pastoral care activities might look like in real life. Using conversation analysis, we examine video recordings of pastoral care delivery to reveal the ways in which a pastoral carer supports a child's behaviour, social and emotional well-being. The significance of the findings is that those who provide pastoral care can see in close detail what delivery might look like as a real-life encounter, imparting valuable knowledge that can then be applied alongside theory and guidelines to enhance professional practice. Of further significance is that the findings can also show how an interactional analysis of pastoral care work can be used to demonstrate social and emotional learning and that the work being done effectively supports children.